Tanggung Jawab Hukum Atas Pasien Gangguan Jiwa Yang Melarikan Diri Dari Ruang Rawat Inap Rumah Sakit - Mulyono Mulyono; Dewi Setyowati; Kamarudin Kamarudin (Al-Adalah: Jurnal Hukum dan Politik Islam, 2018)
Health jurisdiction at this time is increasingly widespread, people are becoming increasingly aware of their rights protected by law. Juridically the hospital is responsible for all losses caused by negligence of health workers in the hospital. To minimize or eliminate losses due to negligence of medical personnel, hospitals hire employees in accordance with his profession to give direct patient health. In the background there is a legal issue in hospital services, namely legal responsibility for mentally ill patients who have escaped from the inpatient hospital. There will be legality problems and the burden of responsibility to the hospital or guard officer in the inpatient room for mental patients who escape from the hospital inpatient room. The research method used in the research is descriptive normative, using a statute approach and conceptual approach. Legal materials used are a source of primary law (criminal code, civil code, the law of the health sector, and regulations the minister of health) and secondary legal materials (textbooks, literature, the literature related to the discussion). Results of the research showed that responsibility for mental patients who escaped from the room inpatient can be grouped into three groups, namely responsible for the field of hospital, the person in charge is the head of the hospital, responsible for the medical field, the person in charge is each doctor, responsibility of the nursing field, the person in charge is each nurse. Where this is a civil case then becomes the responsibility of the home, and when the criminal case it becomes important responsibility beach offender.